Augmented expression of RUNX1 deregulates the global gene expression of U87 glioblastoma multiforme cells and inhibits tumor growth in mice - Yoel Bogoch; Gilgi Friedlander-Malik; Lior Lupu; Ekaterina Bondar; Nitzan Zohar; Sheila Langier; Zvi Ram; Ido Nachmany; Joseph M Klausner; Niv Pencovich (Tumor Biology, 2017)
Glioblastoma multiforme is the most common and aggressive primary brain tumor in adults. A mesenchymal phenotype was associated with tumor aggressiveness and poor prognosis in glioblastoma multiforme patients. Recently, the transcription factor RUNX1 was suggested as a driver of the glioblastoma multiforme mesenchymal gene expression signature; however, its independent role in this process is yet to be described. Here, we assessed the role of RUNX1 in U87 glioblastoma multiforme cells in correspondence to its mediated transcriptome and genome-wide occupancy pattern. Overexpression of RUNX1 led to diminished tumor growth in nude and severe combined immunodeficiency mouse xenograft tumor model. At the molecular level, RUNX1 occupied thousands of genomic regions and regulated the expression of hundreds of target genes, both directly and indirectly. RUNX1 occupied genomic regions that corresponded to genes that were shown to play a role in brain tumor progression and angiogenesis and upon overexpression led to a substantial down-regulation of their expression level. When overexpressed in U87 glioblastoma multiforme cells, RUNX1 down-regulated key pathways in glioblastoma multiforme progression including epithelial to mesenchymal transition, MTORC1 signaling, hypoxia-induced signaling, and TNFa signaling via NFkB. Moreover, master regulators of the glioblastoma multiforme mesenchymal phenotype including CEBPb, ZNF238, and FOSL2 were directly regulated by RUNX1. The data suggest a central role for RUNX1 as master regulator of gene expression in the U87 glioblastoma multiforme cell line and mark RUNX1 as a potential target for novel future therapies for glioblastoma multiforme.